One Palace, two projects: Mendonça Palace (1900 and 1902) - Varela, Júlia Zurbach (2020)
The Mendonça Palace, located in Lisbon at Rua Marquês da Fronteira, was built for the colonial settler Henrique Mendonça, between 1900 and 1909, according to the design of the architect Miguel Ventura Terra. This article introduces an earlier project for this same  building which, despite not questioning the established chronology, invites us to revise the exclusive attribution of the authorship of  this work to Ventura Terra. The presentation of this first project seeks, more than to question the authorship of Ventura Terra, to  reiterate its fundamental role as a work of reference during the Eclecticism period at the turn of the century, and in this way, to  reaffirm this building as of particular relevance to the study of Ventura’s work, due to the way it confirms the consistent and  informed character of his practice, in the context of a burgeoning architectural profession in Portugal at the beginning of the 20th  century.